1997
DOI: 10.2172/580576
|View full text |Cite
|
Sign up to set email alerts
|

HVDC power transmission environmental issues review

Abstract: Thii report has been reproduced directly from the best available copy. Available to the public from the National Technical Information Servii, U.S. Department of Commerce, 5285 Port Royal Rd., Springfield, VA 22 16 1.This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nof any of their employees, makes any warranty, express or implied, or assumes any legal l i b i l i i or responsibili for the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…The peak value of E using method A is 13.4722 kV/m ;while using method B the interval value is [12.8169,14.1265] kV/m which shows the validity of the interval approach. The slight asymmetry of the field profiles, commonly observed in many outdoor studies [1,3,10,11], may be partly explained by the uncertainty in the value of S as observed here at the zero crossing. The E profiles with uncertainty in H only are shown in Fig.5.…”
Section: Monopolar Casementioning
confidence: 47%
See 4 more Smart Citations
“…The peak value of E using method A is 13.4722 kV/m ;while using method B the interval value is [12.8169,14.1265] kV/m which shows the validity of the interval approach. The slight asymmetry of the field profiles, commonly observed in many outdoor studies [1,3,10,11], may be partly explained by the uncertainty in the value of S as observed here at the zero crossing. The E profiles with uncertainty in H only are shown in Fig.5.…”
Section: Monopolar Casementioning
confidence: 47%
“…This may partly explain the discrepancies which usually observed in outdoor field measurements when compared with calculations [1,3,10,11]. The above analysis demonstrates the accuracy of interval techniques in producing accurate bounds for the output result.…”
Section: Fig 6 Bipolar Lateral Electric Field Profiles With Uncertaimentioning
confidence: 74%
See 3 more Smart Citations